MAPPING STUDENTS' THINKING SYSTEMS IN CRITICAL THINKING BASED ON STEM PROJECT-BASED LEARNING EXPERIENCES - Nehru, Nehru; Purwaningsih, Sri; Riantoni, Cicyn; Ropawandi, Doni; Novallyan, Devie (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Critical thinking is an essential skill for students to develop. The objective of this research is to map students' thinking systems in critical thinking based on STEM project-based learning experiences. The method used is a mixed-method approach with an Embedded Experimental Model. The research subjects are undergraduate students in basic physics at the University of Jambi. Data collection is conducted through tests and interviews. The test instrument employs structured critical thinking questions based on the Halpern Critical Thinking Assessment (HCTA) indicators, while the interview instrument utilizes open-ended questions. Data analysis utilizes paired t-tests and coding to map students' thinking systems. The research results indicate an influence of STEM-PjBL learning on students' critical thinking abilities, supported by the analysis showing a moderate increase in students' critical thinking abilities. Additionally, based on mapping students' thinking systems, there is an increase in thinking system 2 by 56 answers. Moreover, thinking system 2 is nearly equivalent to thinking system 1 except in reasoning. In the fourth question and other aspects of critical thinking abilities, thinking system 2 is comparable to thinking system 1 and even more dominant in question number 3. This demonstrates an enhancement in students' critical thinking abilities after STEM project-based learning. This research provides new insights into the development of student's critical thinking skills, which can be beneficial for curriculum development and teaching practices in the STEM education field.